2009
DOI: 10.1111/j.1365-2249.2009.03925.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic airway inflammation and susceptibility to pneumococcal pneumonia in a murine model with real-timein vivoevaluation

Abstract: SummaryThe relationship between allergic airway inflammation and pneumococcal pneumonia is not well understood. We assessed susceptibility to experimental pneumococcal pneumonia in mice with and without allergic airway inflammation. Susceptibility to pneumococcal pneumonia was evaluated by challenging mice with a bioluminescent Streptococcus pneumoniae strain after sensitization with ovalbumin (OVA), with subsequent monitoring of pneumococcal infection using real-time photonic imaging. Of 46 OVAsensitized mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…OVA sensitization and challenge decreased the numbers of airway neutrophils, decreased lung IL-6 and IL-1␤ expression, and increased the Pseudomonas aeruginosa lung burden at 24 h postinfection (66). Two groups induced Streptococcus pneumoniae lung infection in the context of antecedent OVA sensitization and challenge (68,69). In experiments with a serotype 4 strain of S. pneumoniae, OVA-induced allergic airway inflammation neither enhanced nor impaired lung bacterial clearance or postinfection mortality (69).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…OVA sensitization and challenge decreased the numbers of airway neutrophils, decreased lung IL-6 and IL-1␤ expression, and increased the Pseudomonas aeruginosa lung burden at 24 h postinfection (66). Two groups induced Streptococcus pneumoniae lung infection in the context of antecedent OVA sensitization and challenge (68,69). In experiments with a serotype 4 strain of S. pneumoniae, OVA-induced allergic airway inflammation neither enhanced nor impaired lung bacterial clearance or postinfection mortality (69).…”
Section: Discussionmentioning
confidence: 96%
“…As asthma and allergic airway inflammation are generally thought to increase risk for invasive bacterial infection and pneumonia in humans (63)(64)(65), several groups have determined the effect of allergic airway inflammation induced by OVA sensitization and challenge in mouse models of lung bacterial infection (66)(67)(68)(69). IL-4 and IL-13 expressed during OVA-induced allergic airway inflammation impaired the lung clearance of Mycoplasma pneumoniae by impairing lung IL-6 and Toll-like receptor 2 expression (67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that other studies have demonstrated that the hypereosinophilic state induced by ovalbumin sensitization impairs Pseudomonas clearance in the lung (7). This apparent discrepancy is likely due to the induction of multiple Th2 cytokines in the ovalbumin model, including IL-4, which has recently been shown to promote bacterial growth in vivo (20,23).…”
Section: Discussionmentioning
confidence: 97%
“…The impact of ALI on pulmonary bacterial infections was investigated previously utilizing multiple mouse models, with differing results. Employing in vivo bioluminescent imaging, it was found that ALI reduced the level of pneumococcal burden in the lung, although there was a trend toward enhanced bacterial invasiveness (30). In a pulmonary Pseudomonas infection model, it was reported that OVA sensitization and challenge inhibited antibacterial defenses (31).…”
Section: Discussionmentioning
confidence: 99%